A preparation method for improving the adsorption performance of waste gas adsorption resin

By performing scanning electron microscopy image data analysis on the finished product of waste gas adsorption resin, the channel goodness and collapse coefficient are constructed, and the insulation time of the polymerization reaction is adjusted, which solves the problem of too long waiting time for the detection results in the prior art, and improves the adsorption performance.

CN119306862BActive Publication Date: 2025-04-15HANGZHOU DRY AIR TREATMENT EQUIP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411541927.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-04-15
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

In the prior art, the waiting time for the pore detection results of the exhaust gas adsorption resin is too long, which affects the regulation and control of polymerization reaction conditions and cannot meet the needs of large-scale efficient production.

Method used

By performing scanning electron microscopy image data analysis on the finished product of adsorbed resin, the channel goodness and channel collapse coefficient are constructed, which are used to adjust the insulation time of the polymerization reaction and quickly detect and evaluate the quality of the adsorbed resin.

Benefits of technology

It realizes rapid adjustment of polymerization reaction conditions, improves the adsorption performance of adsorbed resin, and solves the problem of inaccurate pore quality detection results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306862B_ABST
    Figure CN119306862B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of waste gas adsorption material preparation, and specifically to a preparation method for improving the adsorption performance of waste gas adsorption resin, comprising: taking monomers, adding deblocking agents, removing polymerization inhibitors therein, and mixing with porogens and initiators as an oil phase; taking pure water, adding dispersants, dissolving, and adding anti-emulsifiers to prepare an aqueous phase; taking the oil phase and adding it to the aqueous phase, stirring until the oil phase is dispersed into oil droplets of a preset size, then heating and polymerizing, and adjusting the insulation time of the polymerization reaction process according to the pore formation situation; filtering after the reaction, washing with deionized water until the effluent is transparent, sieving to obtain the initial polymer, and removing the porogen, and fully swelling the dried initial polymer with an organic solvent, adding Lewis acid to fully dissolve and heat and keep warm, and filtering and washing to obtain the adsorption resin. The present application can adjust the polymerization temperature and insulation time according to the pore characteristics of the adsorption resin to improve the preparation quality of the adsorption resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of waste gas adsorption material preparation, and in particular to a preparation method for improving the adsorption performance of waste gas adsorption resin. Background Art

[0002] In recent years, adsorption resins have been widely used in the field of waste gas treatment due to their high adsorption capacity, easy regeneration and good stability. The pore size of the adsorption resin is an important factor affecting its waste gas treatment performance, and one of the key processes for the size of the pores and preventing pore collapse is the degree of completion of the polymerization reaction in the preparation process. Therefore, in the production process of adsorption resins, it is necessary to sample the finished adsorption resins, and the testing agency or unit shall conduct pore detection of the adsorption resins. According to the test results, the polymerization reaction conditions in the preparation process are adjusted and controlled, so as to produce adsorption resins with better waste gas adsorption performance.

[0003] However, the waiting time for the test results of the above-mentioned test method usually takes 7-10 working days, which takes too long and seriously affects the adjustment and control of the polymerization reaction conditions. Given the current high demand for adsorption resins, it cannot meet the actual needs of large-scale and efficient production.

[0004] In order to solve this problem, some companies usually set up a quality inspection area in the finished product area and arrange a scanning electron microscope. The companies themselves use the automated testing function of the scanning electron microscope to inspect the finished products. Although this method has a faster detection speed, the automated testing of the scanning electron microscope can usually only assist the company in completing the SEM data collection for the finished products, but cannot evaluate the actual adsorption performance of the adsorption resin based on the collected SEM data, that is, it is impossible to accurately detect the pore formation in the adsorption resin based on the collected data. Summary of the invention

[0005] In order to solve the above technical problems, the present application provides a preparation method for improving the adsorption performance of waste gas adsorption resin to solve the existing problems.

[0006] A preparation method for improving the adsorption performance of waste gas adsorption resin in the present application adopts the following technical scheme:

[0007] An embodiment of the present application provides a preparation method for improving the adsorption performance of waste gas adsorption resin, comprising the following steps:

[0008] Take monomers, add deblocking agent, remove the polymerization inhibitor, and mix with porogen and initiator as oil phase; take pure water, add dispersant, dissolve, and add anti-emulsifier to prepare water phase; take oil phase and add it to water phase, the volume ratio of oil phase to water phase is 1:5, stir until the oil phase is dispersed into oil droplets of preset size, then heat and polymerize, and adjust the insulation time of the polymerization process according to the pore formation situation;

[0009] After the reaction is completed, the mixture is filtered and washed with deionized water until the effluent is transparent, the initial polymer is obtained by sieving, the porogen is removed, and the polymer is dried for later use;

[0010] The dried initial polymer is fully swollen with an organic solvent, and then Lewis acid is added to fully dissolve it, and then the temperature is raised to 120°C and kept warm, and then filtered and washed to obtain an adsorption resin;

[0011] Wherein, the insulation time of adjusting the polymerization reaction process is specifically:

[0012] Obtaining a scanning electron microscope image of the adsorption resin; constructing the pore goodness of the adsorption resin by combining the distance between all arbitrary two pore profiles and the number of pore profiles in the scanning electron microscope image of the adsorption resin with the difference between the slope changes of different pore profiles and the size difference of different pore profiles;

[0013] The pore profiles are clustered according to the degree of shape change of each pore profile. The pore collapse coefficient of the adsorption resin is constructed based on the distance relationship between the clusters and the distance between different pore profiles in each cluster, combined with the fluctuation degree of the slope of the pixel points on the pore profile and the difference in the number of pixel points contained in the pore profile.

[0014] By combining the pore goodness and pore collapse coefficient of the adsorption resin, the quality excellence of the adsorption resin is constructed and the insulation time of the polymerization reaction in the adsorption resin preparation process is adjusted.

[0015] Preferably, the monomer is commercial divinylbenzene, and the concentration of divinylbenzene in the monomer is 70wt%; the deblocking agent is sodium hydroxide, the porogen is toluene porogen, and the volume ratio of the oil phase is 30%, and the initiator is diformyl peroxide, and the amount of the initiator accounts for 1.1% of the amount of the monomer.

[0016] Preferably, the weight of the dispersant is 0.18% of the weight of water, the weight of the demulsifier is 0.5% of the weight of water, the dispersant is polyvinyl alcohol, and the demulsifier is 0.1wt% of methylene blue.

[0017] Preferably, the heating rate during the temperature-raising polymerization process is: 5°C / 10min, heating to 50°C, then heating to 78°C at 2°C / 5min, keeping warm for 5h, then heating to 85°C at 4°C / 10min, keeping warm for 8h, then heating to 99°C at 5°C / 10min and keeping warm.

[0018] Preferably, the organic solvent is dichloromethane, the organic solvent is 8 times the weight of the initial polymer after drying, and the Lewis acid is 0.4 times the weight of the initial polymer after drying.

[0019] Preferably, the calculation formula for the pore goodness of the adsorption resin is:

[0020] Wherein, B is the mean of the distances between any two pore profiles, where each pore profile is obtained by edge detection of the adsorption resin scanning electron microscope image; C is the total number of pore profiles; E is the sum of the differences in the mean values ​​of the pixel slopes between any two pore profiles; and F is the average value of the differences in the number of pixels between any two pore profiles.

[0021] Preferably, the clustering of the pore profiles according to the degree of shape change of each pore profile further comprises:

[0022] The mean value of the pixel slope on each channel contour is used as the input of the clustering algorithm to cluster the channel contours and obtain each cluster.

[0023] Preferably, the calculation formula of the pore collapse coefficient of the adsorption resin is:

[0024] Wherein, L is the mean of the distance between any two clusters; K is the cumulative sum of the means of the distance between any two channel contours contained in all clusters; the variance of the slopes of all pixels on each channel contour is analyzed, and M is the cumulative sum of the variances of all channel contours; N is the cumulative sum of the difference in the number of pixels between the channel contour with the largest number of pixels and all other channel contours.

[0025] Preferably, the quality excellence of the adsorption resin is the ratio of the pore goodness to the pore collapse coefficient.

[0026] Preferably, the step of adjusting the polymerization reaction insulation time in the adsorption resin preparation process further comprises:

[0027] If the normalized adsorption resin quality excellence is greater than or equal to a preset threshold, the insulation time of the polymerization reaction is not adjusted; otherwise, the insulation time of the polymerization reaction is extended.

[0028] This application has at least the following beneficial effects:

[0029] This application obtains scanning electron microscope image data of the adsorbent resin by sampling and testing the finished products of the adsorbent resin, and constructs the pore quality and pore collapse coefficient according to the characteristics of the pore formation and pore collapse characteristics of the adsorbent resin, which are used to characterize the goodness of the pores formed by the polymerization reaction during the production of the adsorbent resin and the degree of pore collapse that may occur during the insulation of the polymerization reaction. The adsorbent resin quality excellence is further constructed to characterize the quality of the adsorbent resin prepared this time. The DCS system uses this as a basis to judge the goodness of the polymerization reaction during the preparation process, and then controls the insulation time parameters of the polymerization kettle. This application solves the problem of inaccurate pore quality detection results when using a scanning electron microscope to detect the quality of the adsorbent resin, and realizes a method in which the quality of the finished product can be quickly detected and evaluated during the large-scale production of the adsorbent resin, and then the polymerization reaction conditions can be quickly adjusted, thereby improving the adsorption performance of the prepared adsorbent resin. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions and advantages in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0031] Figure 1 A flowchart of the steps of a preparation method for improving the adsorption performance of waste gas adsorption resin provided in this application;

[0032] Figure 2 A schematic diagram of the uniform distribution characteristics of the normal pore profile of the adsorption resin provided in this application;

[0033] Figure 3 This is a schematic diagram of the difference in pore profiles between a normal pore, an incomplete pore, and a collapsed pore provided in this application;

[0034] Figure 4 A schematic diagram showing the difference between a normal pore profile and a collapsed but unclosed pore profile provided in this application;

[0035] Figure 5 A schematic diagram of the process for adjusting the insulation time of the polymerization reaction in the adsorption resin preparation process provided in the present application. DETAILED DESCRIPTION

[0036] In order to further explain the technical means and effects adopted by the present application to achieve the predetermined invention purpose, the following is a detailed description of the preparation method for improving the adsorption performance of the waste gas adsorption resin proposed in the present application, its specific implementation method, structure, characteristics and effects, in combination with the accompanying drawings and preferred embodiments. In the following description, different "one embodiment" or "another embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.

[0037] Unless otherwise defined, terms such as "comprises", "comprising" or any other variants thereof are intended to cover non-exclusive inclusion, so that a circuit structure, article or device comprising a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such articles or devices. In the absence of further restrictions, an element defined by the statement "comprising a ..." does not exclude the presence of other identical elements in the article or device comprising the element. In addition, the term "and\or" used herein includes any and all combinations of one or more related listed items. All technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present application belongs.

[0038] The following is a detailed description of a specific method for preparing a waste gas adsorption resin for improving its adsorption performance provided by the present application in conjunction with the accompanying drawings.

[0039] An embodiment of the present application provides a preparation method for improving the adsorption performance of waste gas adsorption resin. For details, please refer to Figure 1 , including the following steps:

[0040] Example:

[0041] S1: Take monomer, add deblocking agent, remove the polymerization inhibitor therein, and mix with porogen and initiator as oil phase. The monomer is commercial divinylbenzene, the concentration of divinylbenzene in the monomer is 70wt%, the deblocking agent is sodium hydroxide, the porogen is toluene porogen, the volume ratio of which accounts for 30% of the total volume of the oil phase, and the initiator is diformyl peroxide, and the amount of initiator accounts for 1.1% of the amount of monomer.

[0042] S2: Take pure water, add dispersant, dissolve, and then add demulsifier to prepare the water phase. The weight of dispersant is 0.18% of the weight of water, the weight of demulsifier is 0.5% of the weight of water, the dispersant is polyvinyl alcohol, and the demulsifier is 0.1wt% of methylene blue.

[0043] S3: Take the oil phase and add it to the water phase and let it stand. In this embodiment, let it stand for 3 minutes, and the volume ratio of the oil phase to the water phase is 1:5; start stirring. In this embodiment, adjust the speed until the oil phase is stably dispersed into 0.5mm oil droplets, and then heat up for polymerization. The heating rate is: 5℃ / 10min, heat to 50℃, then heat to 78℃ at 2℃ / 5min, keep warm for 5h, then heat to 85℃ at 4℃ / 10min, keep warm for 8h, then heat to 99℃ at 5℃ / 10min, keep warm for 3 to 10h. In this embodiment, the optimal insulation time of the polymerization reaction is obtained according to the pore formation during the polymerization reaction, and the insulation time of the polymerization reaction process is adjusted.

[0044] S4: After the reaction is completed, the mixture is filtered and washed with 90°C deionized water until the effluent is transparent. In this embodiment, the initial polymer of 0.2 mm is obtained by sieving, and the porogen of the initial polymer is removed. In this embodiment, the porogen is removed by steam stripping. Afterwards, the mixture is dried for use. In this embodiment, the drying method is mainly fluidized bed drying.

[0045] S5: The dried initial polymer is fully swollen with an organic solvent of 8 times its weight, and the swelling time in this embodiment is 12 hours, and then a Lewis acid of 0.4 times the weight of the dried initial polymer is added. After being fully dissolved, the temperature is raised to 120° C. at 1° C. / min in this embodiment and kept warm for 12 hours. The organic solvent is dichloromethane.

[0046] S6: After filtering and washing, the adsorption resin is obtained. Preferably, in this embodiment, the washing method is: washing with anhydrous ethanol until clear and bright, washing with 5wt% hydrochloric acid until clear and bright, and then washing with a large amount of pure water until the pH of the effluent is greater than 4, so that an adsorption resin with high exhaust gas adsorption performance can be obtained.

[0047] Specifically, the steps for adjusting the holding time of the polymerization reaction process in this embodiment are as follows:

[0048] This embodiment takes into account that during the polymerization reaction, the equipment usually directly discharges and feeds materials, and sampling during the reaction is difficult; at the same time, considering that the important factor affecting the pore formation is the polymerization reaction process, it is chosen to perform sampling analysis on the finished product after preparation, and analyze the quality of the adsorption resin based on the pore characteristics of the adsorption resin, and then analyze the insulation time of the polymerization reaction process, so as to adjust the insulation time of the polymerization reaction in the subsequent adsorption resin preparation process.

[0049] Step 1: Obtain a SEM image of the adsorbed resin.

[0050] In order to quickly test the finished product of the adsorption resin, this embodiment sets a quality inspection area in the finished product area of ​​the adsorption resin production process, and arranges a scanning electron microscope in the quality inspection area. The finished product of the adsorption resin is sampled and tested, with a sampling rate of 10%, and the sample is placed in the sample chamber of the scanning electron microscope, the magnification is set to 5000, and the scanning electron microscope image of the adsorption resin sample is obtained.

[0051] Step 2: The pore goodness of the adsorption resin is constructed by the distance between all arbitrary two pore profiles and the number of pore profiles in the SEM image of the adsorption resin, combined with the difference between the slope changes of different pore profiles and the size differences of different pore profiles.

[0052] For the preparation process of the adsorption resin, when the polymerization reaction proceeds well, more pores will be formed on the surface of the adsorption resin, and the pores are evenly distributed without pore collapse. Specifically, in the scanning electron microscope image of the adsorption resin, the pore contours are evenly distributed in the image, and the morphology of each pore contour is similar and relatively full. Figure 2 When pore collapse occurs, the pore profile in the adsorbed resin scanning electron microscope will undergo irregular deformation, resulting in a decrease in the similarity of the pore morphology. Different degrees of collapse produce different degrees of deformation. The greater the irregularity of the pore profile, the greater the degree of collapse. The schematic diagram of the difference in pore profiles when the pores are normal, incompletely generated, and collapsed is as follows: Figure 3 As shown, Figure 3 In the figure, number 1 is the collapsed channel profile, number 2 is the normal channel profile, and number 3 is the incompletely generated channel profile.

[0053] The adsorbed resin scanning electron microscope image is used as input, and the Canny edge detection algorithm and the expansion corrosion algorithm are used to output the edges in the adsorbed resin scanning electron microscope image. All the detected edges are then used as input, and the contour tracking algorithm is used to obtain all the closed contour edges. Each closed contour edge is a channel contour. The Canny edge detection algorithm, the expansion corrosion algorithm, and the contour tracking algorithm are all well-known technologies, and the process is not repeated in this embodiment.

[0054] Therefore, this embodiment will calculate the pore uniformity and pore morphology approximation based on the pore characteristics of the above-mentioned adsorption resin during the polymerization process.

[0055] First, this embodiment determines the pore uniformity A by the distance between any two pore contours and the number of pore contours in the SEM image of the adsorption resin. The specific calculation method is:

[0056] B is the mean distance between any two channel profiles; C is the total number of channel profiles;

[0057] It should be noted that the distance between any two channel contours is the distance between the center points of the any two channel contours. In this embodiment, the distance calculation adopts the Euclidean distance. In actual application, the implementer can select it at will.

[0058] When preparing the adsorption resin, the better the degree of polymerization reaction, the more channels are formed, and the distribution of channels is more uniform and dense, and the distance between the contours of each channel is smaller, which means that the adsorption resin prepared at present has higher uniformity of channels.

[0059] When the polymerization reaction proceeds well during the insulation process of the adsorption resin preparation, the formed pores are similar in size, full in shape and close to circular or elliptical, and the similarity between each contour is high. However, when the insulation time is too short during the insulation process, resulting in incomplete polymerization reaction, the formed pores may have locally smaller pores, incomplete pores, and irregular pore contours, which in turn leads to a decrease in the overall similarity of the pore contours.

[0060] Based on the above characteristics, the channel morphology approximation D is determined by the difference between the slope change degrees of different channel profiles and the size difference of different channel profiles. The specific calculation method is:

[0061] Where, E is the cumulative sum of the differences in the mean values ​​of the pixel slopes between any two pore profiles, where the mean value of the pixel slope of each pore profile is the average value of the slopes of all pixels on each pore profile; F is the average value of the differences in the number of pixels between any two pore profiles;

[0062] It should be noted that the calculation method of the mean pixel slope is: curve fitting is performed on all closed contours in the adsorption resin scanning electron microscope image, and the slope of each pixel on all closed contours on the closed contour curve is calculated, and finally the mean slope of all pixel points on a single closed contour is calculated.

[0063] The better the degree of reaction of the prepared adsorption resin in the polymerization reaction process, the more similar the pore morphology and size are, the smaller the difference in the mean value of the pixel slope on each pore contour is, and the smaller the difference in the total number of pixels contained in the pore contour is, indicating that the pore morphology of the adsorption resin prepared at this time is more similar.

[0064] In summary, this embodiment will calculate the pore goodness of the adsorption resin by the pore uniformity A and the pore morphology approximation D. The specific calculation method is:

[0065] G is the pore goodness of the adsorption resin, A is the pore uniformity in the current adsorption resin scanning electron microscope image; D is the pore morphology similarity in the current adsorption resin scanning electron microscope image; the stronger the adsorption performance of the prepared adsorption resin, the higher the pore uniformity formed during the polymerization reaction, and the higher the morphology similarity between each pore, which means that the reaction degree of the polymerization reaction is better, and the reaction conditions of the polymerization reaction do not need to be adjusted for the time being.

[0066] At this point, the pore quality of the current adsorption resin is obtained.

[0067] Step 3: Cluster the pore contours according to the mean slope of all pixels on each pore contour. According to the distance relationship between the clusters and the distance between different pore contours in each cluster, the pore collapse coefficient of the adsorption resin is constructed by combining the fluctuation degree of the slope of the pixel points on the pore contour and the difference in the number of pixels contained in the pore contour.

[0068] However, in the process of preparing the adsorption resin, the polymerization reaction needs to be carried out for a long time and then heated up. During this process, the pores will gradually form as the polymerization reaction proceeds. If the control conditions of the polymerization reaction deviate, the pores will collapse, which will affect the performance of the adsorption resin. When the degree of influence of pore collapse varies, there are also large differences in the characteristics of the formed adsorption resin scanning electron microscope image. When the pore collapse is more serious, most of the pores will be closed, and then the pore contour in the adsorption resin scanning electron microscope image will be sharply reduced. At this time, the calculation of the pore goodness can better reflect the pore collapse. However, when the pore collapse is relatively mild or only occurs locally, there are not only normal pores in the adsorption resin scanning electron microscope image, but also many collapsed but not completely closed pores. At this time, the calculated pore goodness is relatively high, and it is difficult to judge the actual pore goodness, so further analysis is needed.

[0069] Schematic diagram of the difference between the normal pore outline and the collapsed but unclosed pore outline Figure 4 As shown, Figure 4 In the figure, number 4 represents the pore profiles with different degrees of collapse but not completely closed, and number 5 represents the normal pore profiles.

[0070] Specifically, when the pores collapse locally or slightly, the original full pore profile will undergo a certain degree of irregular deformation, which is specifically manifested as a local change in the pore morphology in the scanning electron microscope image, and the sharpness of the edge of the aperture profile becomes larger. The pore profiles with different degrees of collapse appear to be locally dense and overall dispersed in the overall scanning electron microscope image. In this embodiment, in order to further distinguish the actual collapse of each pore profile in the scanning electron microscope image of the adsorbent resin, the mean of the pixel slope on each pore profile is used as the input of the clustering algorithm. In this embodiment, the DPC clustering algorithm is used, the cutoff distance is set to 3, and the output is a plurality of cluster clusters. The pore profiles contained in each cluster cluster are similar in morphology, that is, the aperture profiles with similar collapse states. The DPC clustering algorithm is a well-known technology, and this application will not repeat its process.

[0071] According to the characteristics existing when the adsorption resin pores collapse during the above-mentioned polymerization process, this embodiment will construct the local collapse degree and the pore collapse coefficient.

[0072] First, the local collapse H is determined by the distance relationship between each cluster and the distance between different channel profiles in each cluster. The specific calculation method is:

[0073] Wherein, L is the mean value of the distance between all arbitrary two clusters; wherein, in this embodiment, the distance between any two clusters is the Euclidean distance between the cluster centers of the arbitrary two clusters;

[0074] K is the cumulative sum of the means of the distances between any two pore profiles contained in all clusters; α is a parameter to prevent the denominator from being 0, α = 0.001.

[0075] If the polymerization reaction conditions in the adsorption resin preparation process are not suitable, the pores of the adsorption resin may collapse, and the pore contours of various collapse degrees are locally distributed more densely and the overall distribution is more discrete. The greater the distance between clusters, but the smaller the distance between pore contours within clusters, the greater the corresponding local collapse degree.

[0076] Furthermore, the collapse coefficient P is determined by the fluctuation degree of the slope of the pixel points on the pore contour and the difference in the number of pixel points contained in the pore contour. The specific calculation method is:

[0077] Among them, the variance of the slope of all pixels on each channel contour is analyzed, M is the cumulative sum of the variances of all channel contours; N is the cumulative sum of the differences in the number of pixels between the channel contour containing the largest number of pixels and all other channel contours.

[0078] If the reaction conditions of the polymerization reaction are not suitable during the preparation of the adsorption resin, the pores formed by the adsorption resin may collapse locally. The more serious the collapse, the more the pore size profile of the adsorption resin is affected, the greater the degree of morphological change, the greater the difference in the slope of the pixel points on the pore profile, and the greater the degree of reduction in the size of the pore profile, that is, the greater the collapse coefficient.

[0079] Based on the above analysis, in order to characterize the local collapse characteristics of the current pores, the pore collapse coefficient Z of the adsorption resin is constructed according to the local collapse coefficient and the collapse degree coefficient. The specific calculation method is: That is, Z=H+P; where H is the local collapse coefficient and P is the collapse degree coefficient.

[0080] When preparing the adsorption resin, the greater the possibility of local collapse, the larger the local collapse coefficient, the more serious the collapse, the larger the collapse degree coefficient, that is, the larger the local collapse coefficient of the pore size, indicating that the polymerization reaction conditions may be inappropriate during the preparation of the adsorption resin. Therefore, the pore quality of the prepared adsorption resin is worse and the adsorption performance is weaker.

[0081] At this point, the pore collapse coefficient of the adsorption resin is obtained.

[0082] Step 4: Based on the pore goodness and pore collapse coefficient of the adsorption resin, the quality excellence of the adsorption resin is constructed, and the polymerization reaction insulation time in the adsorption resin preparation process is adjusted.

[0083] Finally, this embodiment will analyze the resin quality of the adsorption resin according to the pore goodness and pore collapse coefficient of the adsorption resin, and construct the adsorption resin quality excellence X, wherein the adsorption resin quality excellence is the ratio of the pore goodness to the pore collapse coefficient.

[0084] It can be understood that the more suitable the conditions of the polymerization reaction during the preparation of the adsorption resin, the better the pores formed in the adsorption resin, the smaller the possibility of pore collapse, the smaller the pore collapse coefficient, the higher the performance of the prepared adsorption resin, that is, the greater the quality of the adsorption resin.

[0085] At this point, the quality of the adsorption resin is excellent.

[0086] Furthermore, the quality excellence of the adsorption resin obtained in the above process is normalized to the maximum and minimum, its value range is normalized to between [0,1], and the normalized result is used as the quality test result of the adsorption resin for this sampling test.

[0087] Furthermore, this embodiment will set a preset threshold value U. In this embodiment, U is set to 0.6, and the implementer can adjust it according to time requirements. When the quality excellence of the adsorption resin is greater than or equal to the preset threshold, the pore quality of the adsorption resin produced this time is higher and the adsorption performance is stronger. At this time, the insulation time for the polymerization reaction in the preparation process is appropriate, and there is no need to adjust the preparation link of the polymerization reaction; when the quality excellence of the adsorption resin is less than the preset threshold, the insulation time of the polymerization reaction is extended until the quality excellence of the adsorption resin is greater than or equal to the preset threshold, so as to ensure the quality of the pore formation of the adsorption resin, ensure the normal progress of the polymerization reaction when the next batch of adsorption resin is prepared, improve the quality of the pores of the prepared adsorption resin, and improve the adsorption performance of the adsorption resin.

[0088] Specifically, the schematic diagram of the polymerization reaction heat preservation time adjustment process of the adsorption resin preparation process is as follows Figure 5 shown.

[0089] In order to better reflect the preparation effect of this embodiment, 5 batches of adsorption resins were produced by adjusting the polymerization reaction insulation time in this embodiment, and then 5 comparative examples were set. The difference between the comparative examples and this embodiment is that the polymerization reaction insulation time in comparative examples 1, 2, 3, 4, and 5 is fixedly set to 3h, 4h, 8h, 9h, and 10h, respectively, and the other parameters are set the same, and each comparative example produces 1 batch of adsorption resin. The above 10 batches of adsorption resins were sampled and tested, and the sampling rate was 10%. The comparison of the pore diameters of the adsorption resins produced by this embodiment and comparative examples 1, 2, 3, 4, and 5 is shown in Table 1.

[0090] Table 1

[0091]

[0092] It can be seen from Table 1 that the pore size of the pores in the adsorption resin produced by the method of this embodiment is significantly larger than that of the adsorption resin produced by the comparative example.

[0093] It is understood that references to "one embodiment" or "some embodiments" etc. described in the specification of the present application mean that one or more embodiments of the present application include specific features, structures or characteristics described in conjunction with the embodiment. Therefore, if "in one embodiment", "in some embodiments", "in some other embodiments", "in some other embodiments", etc. appear in different places in this specification, they do not necessarily refer to the same embodiment, but mean "one or more but not all embodiments", unless otherwise specifically emphasized in other ways. The terms "including", "comprising", "having" and their variations all mean "including but not limited to", unless otherwise specifically emphasized in other ways.

[0094] It should be noted that the sequence of the above-mentioned embodiments of the present application is only for description and does not represent the advantages and disadvantages of the embodiments. And the above-mentioned specific embodiments of this specification are described. In addition, the process depicted in the accompanying drawings does not necessarily require the specific order or continuous order shown to achieve the desired results. In some embodiments, multi-tasking and parallel processing are also possible or may be advantageous. At the same time, the size of the sequence number of each step in the embodiment does not mean the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments in this specification.

[0095] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application, and should all be included in the protection scope of the present application.

Claims

1. A preparation method for improving the adsorption performance of waste gas adsorption resin, characterized in that: The following steps are involved: Take monomers, add deblocking agent, remove the polymerization inhibitor, and mix with porogen and initiator as oil phase; take pure water, add dispersant, dissolve, and add anti-emulsifier to prepare water phase; take oil phase and add it to water phase, the volume ratio of oil phase to water phase is 1:5, stir until the oil phase is dispersed into oil droplets of preset size, then heat and polymerize, and adjust the insulation time of the polymerization process according to the pore formation situation; After the reaction is completed, the mixture is filtered and washed with deionized water until the effluent is transparent, the initial polymer is obtained by sieving, the porogen is removed, and the polymer is dried for later use; The dried initial polymer is fully swollen with an organic solvent, and then Lewis acid is added to fully dissolve it, and then the temperature is raised to 120°C and kept warm, and then filtered and washed to obtain an adsorption resin; Wherein, the insulation time of adjusting the polymerization reaction process is specifically: Obtaining a scanning electron microscope image of the adsorption resin; constructing the pore goodness of the adsorption resin by combining the distance between all arbitrary two pore profiles and the number of pore profiles in the scanning electron microscope image of the adsorption resin with the difference between the slope changes of different pore profiles and the size difference of different pore profiles; The pore profiles are clustered according to the degree of shape change of each pore profile. The pore collapse coefficient of the adsorption resin is constructed based on the distance relationship between the clusters and the distance between different pore profiles in each cluster, combined with the fluctuation degree of the slope of the pixel points on the pore profile and the difference in the number of pixel points contained in the pore profile. By combining the pore goodness and pore collapse coefficient of the adsorption resin, the quality excellence of the adsorption resin is constructed and the insulation time of the polymerization reaction in the adsorption resin preparation process is adjusted.

2. A method for preparing a waste gas adsorption resin for improving adsorption performance according to claim 1, characterized in that: The monomer is commercial divinylbenzene, and the concentration of divinylbenzene in the monomer is 70wt%; the deblocking agent is sodium hydroxide, the porogen is toluene porogen, and the volume ratio of the oil phase is 30%, and the initiator is diformyl peroxide, and the amount of the initiator accounts for 1.1% of the amount of the monomer.

3. A method for preparing a waste gas adsorption resin for improving adsorption performance according to claim 1, characterized in that: The weight of the dispersant is 0.18% of the weight of water, the weight of the demulsifier is 0.5% of the weight of water, the dispersant is polyvinyl alcohol, and the demulsifier is 0.1wt% of methylene blue.

4. A method for preparing a waste gas adsorption resin for improving adsorption performance according to claim 1, characterized in that: During the temperature-raising polymerization process, the heating rate is 5°C / 10min, the temperature is raised to 50°C, then raised to 78°C at 2°C / 5min, kept warm for 5h, then raised to 85°C at 4°C / 10min, kept warm for 8h, then raised to 99°C at 5°C / 10min and kept warm.

5. A method for preparing a waste gas adsorption resin for improving adsorption performance according to claim 1, characterized in that: The organic solvent is dichloromethane, the organic solvent is 8 times the weight of the initial polymer after drying, and the Lewis acid is 0.4 times the weight of the initial polymer after drying.

6. A method for preparing a waste gas adsorption resin for improving adsorption performance according to claim 1, characterized in that: The calculation formula of the pore goodness of the adsorption resin is: ; Wherein, B is the mean distance between any two pore profiles, where each pore profile is obtained by edge detection of the adsorption resin scanning electron microscope image; C is the total number of pore profiles; E is the sum of the differences in the mean values ​​of the pixel slopes between any two pore profiles; and F is the average value of the differences in the number of pixels between any two pore profiles.

7. A method for preparing a waste gas adsorption resin for improving adsorption performance according to claim 1, characterized in that: The clustering of each channel profile according to the degree of shape change of each channel profile further includes: The mean value of the pixel slope on each channel contour is used as the input of the clustering algorithm to cluster the channel contours and obtain each cluster.

8. The method for preparing a waste gas adsorption resin for improving adsorption performance according to claim 1, characterized in that: The calculation formula of the pore collapse coefficient of the adsorption resin is: ; Wherein, L is the mean of the distance between any two clusters; K is the cumulative sum of the mean of the distance between any two channel profiles contained in all clusters; the variance of the slopes of all pixels on each channel profile is analyzed, M is the cumulative sum of the variances of all channel profiles; N is the cumulative sum of the difference in the number of pixels between the channel profile with the largest number of pixels and all other channel profiles, To prevent the denominator from being zero, .

9. A method for preparing a waste gas adsorption resin for improving adsorption performance according to claim 1, characterized in that: The quality excellence of the adsorption resin is the ratio of the pore goodness to the pore collapse coefficient.

10. The method for preparing a waste gas adsorption resin for improving adsorption performance according to claim 1, characterized in that: The step of adjusting the polymerization reaction insulation time in the adsorption resin preparation process further comprises: If the normalized adsorption resin quality excellence is greater than or equal to a preset threshold, the insulation time of the polymerization reaction is not adjusted; otherwise, the insulation time of the polymerization reaction is extended.

Citation Information

Patent Citations

  • Porous material hole automatic measurement method based on scanning electron microscope image segmentation

    CN111524181A

  • High-specific-surface-area adsorption resin with multistage pore size distribution as well as preparation method and application thereof

    CN115945181A